2008
DOI: 10.1002/jobm.200800004
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nature of the enzymes involved in catabolism of caffeine and related methylxanthines

Abstract: Previously isolated strain of Pseudomonas sp. has the capability of utilizing caffeine as the sole source of carbon and nitrogen and degrading caffeine at higher concentrations (>10 g l(-1)). In this study, an assay has been developed to study the enzymatic conversion of caffeine to subsequent methylxanthines by cell free extracts of Pseudomonas sp., the activity of which has been stabilized by use of stabilizers in the lysis buffer. Growth of the strain in various methylxanthines and later enzyme assay demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 20 publications
4
21
0
Order By: Relevance
“…For instance, when caffeine-degrading Pseudomonas sp. strain NCIM5235 was grown with theobromine as the sole source of carbon and nitrogen, the caffeine N-demethylase and theobromine N-demethylase activities in cell extracts were 10-fold lower and 3-to 4-fold higher, respectively, than those in cell extracts from caffeine-grown cells (2). Caffeine dehydrogenase activity in Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, when caffeine-degrading Pseudomonas sp. strain NCIM5235 was grown with theobromine as the sole source of carbon and nitrogen, the caffeine N-demethylase and theobromine N-demethylase activities in cell extracts were 10-fold lower and 3-to 4-fold higher, respectively, than those in cell extracts from caffeine-grown cells (2). Caffeine dehydrogenase activity in Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 95%
“…Caffeine and theobromine also did not inhibit 7-methylxanthine N demethylation by this enzyme. A recent study by Dash and Gummadi (2) showed that caffeine and theobromine N-demethylases in Pseudomonas sp. strain NCIM5235 were inducible in nature, but the caffeine N-demethylase activity in theobromine-grown cells was 10-fold lower than that in caffeine-grown cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some indirect experiments by others indicate the presence of specific, maybe multiple N-demethylases in caffeine-degrading bacteria. A recent study by Dash & Gummadi (2008) showed that caffeine and theobromine N-demethylases in Pseudomonas sp. NCIM 5235 were inducible in nature but caffeine N-demethylase activity in theobromine-grown cells was 10-fold lower than that of caffeine-grown cells.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these belong to the genus Pseudomonas (Asano et al, 1993;Blecher & Lingens, 1977;Dash & Gummadi, 2008;Sideso et al, 2001;Woolfolk, 1975;Yu et al, 2009); however, a strain of Serratia marcescens was also found to N-demethylate caffeine (Mazzafera et al, 1996). N-Demethylation of caffeine in bacteria results in production of either theobromine (3,7-dimethylxanthine) or paraxanthine (1,7-dimethylxanthine).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the enzymes involved in caffeine degradation are also not explicit, with the exception of caffeine oxidase, which has been purified and characterized [24,29]. A few studies have shown there might be separate enzymes, acting separately [1,14] or as a complex [3,12], which bring about specific demethylations in Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 97%